2019
DOI: 10.4491/eer.2018.414
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variations and source apportionment of NOx, SO2, and O3 emissions around heavily industrial locality

Abstract: The main objective of this study is to estimate the levels of pollution to which the community is presently exposed and to model the regimes of local air quality. Diurnal, daily, and monthly variations of NO, NO2, SO2, and O3 were thoroughly investigated in three areas; namely, residential, industrial, and terminal in Ras Al-Khafji. There is obvious diurnal variation in the concentration of these pollutants that clearly follows the diurnal variation of atmospheric temperature and main anthropogenic and industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…5(d)). However, the diurnal variation distribution of SO 2 is different from the bimodal distribution in some studies [25,57], due to the fact that Nanchong City is a large agricultural city with underdeveloped industries, and the phenomenon of morning and evening peak caused by human activities is not obvious. SO 2 concentration in the evening is substantially higher than that in the daytime because of the existence of SO 2 in the evening and the better conditions for pollutant diffusion in the daytime than in the evening [60].…”
Section: Diurnal Variation Characteristicsmentioning
confidence: 77%
See 2 more Smart Citations
“…5(d)). However, the diurnal variation distribution of SO 2 is different from the bimodal distribution in some studies [25,57], due to the fact that Nanchong City is a large agricultural city with underdeveloped industries, and the phenomenon of morning and evening peak caused by human activities is not obvious. SO 2 concentration in the evening is substantially higher than that in the daytime because of the existence of SO 2 in the evening and the better conditions for pollutant diffusion in the daytime than in the evening [60].…”
Section: Diurnal Variation Characteristicsmentioning
confidence: 77%
“…Under high temperature and strong solar radiation, NOx and VOCs easily develop photochemical reactions to produce O 3 [5,56]. Wind also has a positive effect on O 3 [31,57]; specifically, there is an obvious positive correlation between wind speed and O 3 (r = 0.44, p < 0.01) (Table S3). For this reason, O 3 concentration in spring and summer increases greatly, and the peak concentration occurs in July and August.…”
Section: Monthly Variation Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the multiple comparison test confirmed that the red cluster (CL1) contributed more to the concentrations of SO 2 , which is associated with emissions from heavy and light vehicle traffic, with contributions from the CMLO and with emissions from train traffic. Clusters 2 and 3 also showed significant differences at 5%; however, their average values and behavior are similar, which may indicate predominant emission sources with similarity for both clusters or the absence of important sources in the directions they represent (Al-Harbi et al, 2020 ). The Mann–Whitney U test proves to be an effective tool for determining significant differences between clusters (Chávez, 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…Natural emission sources include lightning, which promotes the transformation of nitrogen into nitrogen oxides, and forest fires, which lead to the combustion of biomass and the production of NO 2 [7]. Human activities, such as the burning of fossil fuels and industrial activities, are the main causes of increases in NO 2 concentrations in the troposphere [8]. Therefore, in areas such as eastern China, eastern US, eastern India, and the Persian Gulf, where the population is relatively large, transportation networks are well developed, and industrialization is relatively concentrated, high concentrations of NO 2 are typically found [9,10].…”
Section: Introductionmentioning
confidence: 99%